Blepharita amica - Dubatolov, V. V.; Zinchenko, V. K; Ustjuzhanin, P. Ya. (Zenodo, 2023)
Blepharita amica (Treitschke, 1825) MATERIAL. Russia : Kunashir Island, Danilovskii kordon, 8-13.X 2022, 4 ♂; Andreevskii kordon, 14-24.X 2022, 9 ♂, 1 ♀. DISTRIBUTION. One more widely distributed transpalearctic species; the easternmost localities are: Sakhalin, Japan: Hokkaido, Honshu (Eda & Shikata, 2011). Published as part of Dubatolov, V. V., Zinchenko, V. K & Ustjuzhanin, P. Ya., 2023, Autumn moths and butterflies (Lepidoptera) new for the fauna of Kunashir Island, pp. 11-24 in Far Eastern Entomologist 474 on page 19, DOI:10.25221/fee.474.3, http://zenodo.org/record/7945971